Slogovni pluralizem v delih Karola Pahorja - Koter, Darja (Muzikološki zbornik, 2018)
Karol Pahor (1896-1974) stood out on several levels and is recognized as one of the most distinguished students of Slavko Osterc, his opus shows the stylistic diversity resulting from various factors. As a composer he deviates from the usual stereotypes, the standard being that the composer relies on his teacher during his formative years then sharpens and profiles in his own direction which leads him forward and often changes with the new contemporary compositional schools. This article attempts to determine what patterns and views he had through different periods and how he was shaped as a composer by the environment in which he lived and worked.
Keywords: avantgardna glasba; Osterc, Slavko; Pahor, Karol; slogovni pluralizem; slovenski skladatelji; tradicionalna glasba